A Resolution of the City Council of the City of Oxnard Providing for Reimbursement of Actual and Necessary Expenses - Joseph W. Hodges, Jr.:::::: (1975)
A resolution which outlined the requirements for a council member or the spouse of a council member to be reimbursed for expenses caused by official duties.